Diagnosis of Life-Threatening Alpha-Gal Food Allergy Appears to Be Patient Driven - Mary Grace Flaherty PhD, MS; Samantha Jan Kaplan MLIS; Maya R. Jerath MD, PhD (SAGE Publishing, 2017)
Objective: Patients exhibiting life-threatening symptoms associated with the alpha-gal food allergy (delayed urticaria or anaphylaxis due to mammalian meat) are frequently undiagnosed, causing unnecessary emergency department (ED) and health care visits, and extensive pain and suffering. This study aimed to determine the path to diagnosis experienced by alpha-gal patients. Methods: Semistructured interviews were conducted from March to June 2016 with a chronological systematic sample of approximately 10% of patients diagnosed with alpha-gal and treated by the University of North Carolina Allergy and Immunology Clinic (n = 28). Main outcome measures included average length of time between first symptoms' appearance and diagnosis, number and type of health care encounters en route to diagnosis, and typical symptom severity. Results: Six interviewees (21%) were diagnosed within a year of experiencing symptoms, of the remaining 22, mean time to diagnosis was 7.1 years. In over 100 medical encounters (including 28 ED visits and 2 urgent care) the correct diagnosis or effective diagnosing referral occurred less than 10% of the time. Seventy-one percent (20/28) described their first symptoms as severe. More patients found the allergist specializing in this condition on their own (n = 12; 43%) than those who were formally diagnosed or received referrals (n = 10; 36%) through the health care system. Conclusions: The medical community is challenged to stay abreast of emerging and newly uncovered illnesses through traditional medical literature communication channels. Presently, patients more often discover a diagnosis of alpha-gal allergy by using information resources on their own than by presenting to the ED with anaphylaxis.